2021
DOI: 10.1111/ggi.14330
|View full text |Cite
|
Sign up to set email alerts
|

Social frailty is independently associated with geriatric depression among older adults living in northern Japan: A cross‐sectional study of ORANGE registry

Abstract: To clarify prevalence of social frailty among older adults living in a rural Japanese community, and factors associated with social frailty status.Methods: In total, 322 adults aged ≥65 years living in a Japanese rural community took part in the study from 2018 to 2020. Social frailty was defined as deficiencies of: (i) living alone; (ii) talking with someone every day; (iii) feeling helpful to friends or family; (iv) going out less frequently compared with last year; and (v) visiting friends sometimes. Social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Table A1 and Table A2 show the characteristics of the studies included in the review. Of the 14 original studies, 9 are cross-sectional studies [ 4 , 11 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], 3 are prospective cohort studies [ 8 , 25 , 26 ], and 1 is a retrospective cohort study [ 27 ]. One analyzed both cross-sectional data and data from prospective cohort studies [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table A1 and Table A2 show the characteristics of the studies included in the review. Of the 14 original studies, 9 are cross-sectional studies [ 4 , 11 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], 3 are prospective cohort studies [ 8 , 25 , 26 ], and 1 is a retrospective cohort study [ 27 ]. One analyzed both cross-sectional data and data from prospective cohort studies [ 10 ].…”
Section: Resultsmentioning
confidence: 99%
“…Depression: 15-item Geriatric Depression Scale-Short Form Korean Version (GDSSF-K) Depression was significantly correlated with social frailty. Yu Kume (2022) [ 23 ] To clarify prevalence of social frailty among older adults living in a rural Japanese community, and factors associated with social frailty status. cross-sectional study; Level 3 N = 322 aged 65 or older in a Japanese rural community 1.…”
Section: Table A1mentioning
confidence: 99%
“…Living alone, which is one criterion for social isolation in our study, was reported to be associated with lower processing speed and more severe depressive symptoms ( Gow, Corley, Starr, & Deary, 2013 ). And attentional function assessed by trail making test- part A was associated with depressive symptoms in Japanese older adults with social frail ( Kume et al., 2022 ). Depressive symptoms are also known to mediate a decrease in serum brain-derived neurotrophic factor concentrations and brain volume, resulting in a decrease in processing speed as assessed by the symbol digit substitution task (H. Shimada et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of psychological and cognitive frailty, geriatric depression was found to be a predictor of productive role among the young-old adults. A previous study found that geriatric depression was an independent variable for social frailty [ 13 ]. Social frailty was defined as living alone, talking with someone every day, feeling helpful to friends or family, going out less frequently compared with the previous year, and visiting friends sometimes [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, engagement in productive roles as a trigger for social participation in old age may assist in the prevention of frailty. Several previous studies indicated that social frailty was associated with depressive symptoms [ 13 ] in addition to physical and cognitive functions [ 14 ]. However, few studies have examined the engagement of older adults in productive roles, including paid (full-time or part-time), unpaid, and volunteer work.…”
Section: Introductionmentioning
confidence: 99%